Improving Conservative Treatment of Laryngotracheitis in Children - Kamol oʻgʻli, Muxtorov Anvar; A. I., Boltaev (Journal of Science in Medicine and Life, 2025)
Laryngotracheitis is an inflammatory lesion of the mucous membrane of the larynx and trachea, which leads to swelling, spasm of the upper respiratory tract, voice impairment, and a rough "ringing" cough. This disease develops independently or is a complication of other upper respiratory tract infections: ARVI, measles, whooping cough, scarlet fever, etc. In severe cases of laryngotracheitis, the patient may need emergency care.